Cementation of a dual-mobility cup into a well-fixed cementless shell in patients with high risk of dislocation undergoing revision total hip arthroplasty. Issue 1 (January 2021) - Moreta, Jesús; Uriarte, Iker; Foruria, Xabier; Urra, Ioar; Aguirre, Urko; Martínez-de Los Mozos, José L
Background: Cementation of polyethylene liners into well-fixed cementless metal shells has become an option during revision total hip arthroplasty (THA). We report the results of cementing a dual-mobility (DM) component into a stable acetabular shell in high-risk patients undergoing revision THA. Methods: A single-centre series of 10 patients undergoing revision THA with a DM cup cemented into an existing well-fixed shell between 2012 and 2016 were retrospectively reviewed. Failure due to aseptic loosening or instability and implant survival at last follow-up were analysed. The average age was 79.2 years and mean follow-up was 3.5 years. Indications were recurrent hip dislocation in 8 cases and intraoperative instability with moderate abductor insufficiency in 2 cases. In cases with recurrent dislocation, the aetiology of instability was classified by Wera type. Results: At the latest follow-up, Harris Hip Scores had improved from 49.3 preoperatively to 71.3 postoperatively ( p = 0.098). In the 8 patients with recurrent dislocation, 4 cases (50%) had an unclear aetiology (Wera type 6), 2 (25%) abductor deficiency (Wera type 3) and 2 (25%) late polyethylene wear (type 5). Postoperative recurrent dislocation occurred in 1 hip (10%). No cases of intraprosthetic dislocation, aseptic loosening of the previous shell or dissociation at the cement-cup interface were identified. Conclusion: Although the follow-up of this series is short, cementation of a DM cup into a previous well-fixed socket seems to be a viable option to treat and prevent instability after revision THA, without providing constraint at the cement-cup interface.